VANILLIC ACID INHIBITS LUNG CARCINOGENESIS BY MODULATES GLYCOPROTEIN ABNORMALITIES, MEMBRANE-BOUND ENZYMES, AND INFLAMMATORY MARKERS - VELLI, SATHESH KANNA; THIRUVENGADAM, DEVAKI (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The current plan was accompanied to explicate the possible protective role of vanillic acid (VA), on modification in lipid peroxidation, inflammatory cytokines, membrane-bound enzymes, and glycoconjugates during B(a)P induced lung cancer in Swiss albino mice. Methods: Benzo(a)pyrene was administered orally (50 mg/kg b. wt) to induce lung cancer in Swiss albino mice. lipid peroxidation, serum marker enzymes, inflammatory cytokines, membrane-bound ATPases and protein-bound carbohydrate components (Hexose, hexosamine, sialic acid and fucose) and Mast cells and PAS staining were carried out. Results: Lung cancer possessing animals exhibited increased levels of lipid peroxidation, ADA, AHH, γ-GT, 5’-NT, LDH, cytokines such as TNF-α and IL-1β, protein-bound carbohydrate components (protein-hexose, hexosamine, sialic acid, and fucose) also diminished activity of membrane-bound ATPases (Na+/K+ATPases, Ca2+ATPases, and Mg2+ATPase). Treatment with VA significantly ameliorated all these activities. Conclusion: Overall, the present study evidence to the VA has effective anti-inflammatory in addition to free radical scavenging activity for the duration of lung carcinogenesis in Swiss albino mice.